Performance of the MICE diagnostic system. (16th August 2021) - Bogomilov, M.; Tsenov, R.; Vankova-Kirilova, G.; Song, Y.P.; Tang, J.Y.; Li, Z.H.; Bertoni, R.; Bonesini, M.; Chignoli, F.; Mazza, R.; Palladino, V.; de Bari, A.; et al.
Abstract: Muon beams of low emittance provide the basis for the intense, well-characterised neutrino beams of a neutrino factory and for multi-TeV lepton-antilepton collisions at a muon collider. The international Muon Ionization Cooling Experiment (MICE) has demonstrated the principle of ionization cooling, the technique by which it is proposed to reduce the phase-space volume occupied by the muon beam at such facilities. This paper documents the performance of the detectors used in MICE to measure the muon-beam parameters, and the physical properties of the liquid hydrogen energy absorber during running.